2003
DOI: 10.1074/jbc.m300061200
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Arrest Signaling in Response to UV Damage Is Independent of Nucleotide Excision Repair in Saccharomyces cerevisiae

Abstract: The recognition of DNA double-stranded breaks or single-stranded DNA gaps as a precondition for cell cycle checkpoint arrest has been well established. However, how bulky base damage such as UV-induced pyrimidine dimers elicits a checkpoint response has remained elusive. Nucleotide excision repair represents the main pathway for UV dimer removal that results in strand interruptions. However, we demonstrate here that Rad53p hyperphosphorylation, an early event of checkpoint signaling in Saccharomyces cerevisiae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…In addition, checkpoint activation in stationary phase (non-dividing) cultures suggests that unrepaired DNA damage triggers checkpoint activation rather than interference with replication or a DNA repair intermediate, although we cannot rule out a contribution from recombination repair. Similar observations have been made for UV-induced DNA damage (15). In humans, repair-proficient senescent cell cultures are characterized by phosphorylated Chk2 (the human Rad53p homolog), presumably due to telomere erosion (41).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, checkpoint activation in stationary phase (non-dividing) cultures suggests that unrepaired DNA damage triggers checkpoint activation rather than interference with replication or a DNA repair intermediate, although we cannot rule out a contribution from recombination repair. Similar observations have been made for UV-induced DNA damage (15). In humans, repair-proficient senescent cell cultures are characterized by phosphorylated Chk2 (the human Rad53p homolog), presumably due to telomere erosion (41).…”
Section: Discussionsupporting
confidence: 57%
“…Detection of Rad53 by Western Blotting-Yeast protein extracts were prepared following zirconium bead lysis in trichloroacetic acid and Rad53 was visualized by PAGE gel electrophoresis as described previously (15,16). The primary Rad53 antibody used was from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the DNA damage checkpoint monitors the presence of NER intermediates in UVirradiated G 1 and G 2 cells (5, 18-22, 49). However, other studies have suggested that the DNA damage checkpoint monitors pyrimidine dimers in the absence of NER (50,51). After a UV dose of 5 J͞m 2 , which is expected to introduce Ϸ400 pyrimidine dimers per cell, we found that the cell-cycle response of budding yeast and ⌬UVDE fission yeast, both of which excise UV lesions exclusively through NER, occurs only after passage through S phase.…”
Section: Discussionmentioning
confidence: 70%
“…In yeast, however, the NER pathway does not actively recruit checkpoint signaling proteins that respond to UV damage. 7 …”
Section: Nucleotide Excision Repair and G 1 /S Checkpointmentioning
confidence: 99%